2011
DOI: 10.1101/cshperspect.a007559
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Mitochondrial Proteostasis

Abstract: A decline in mitochondrial activity has been associated with aging and is a hallmark of many neurological diseases. Surveillance mechanisms acting at the molecular, organellar, and cellular level monitor mitochondrial integrity and ensure the maintenance of mitochondrial proteostasis. Here we will review the central role of mitochondrial chaperones and proteases, the cytosolic ubiquitin-proteasome system, and the mitochondrial unfolded response in this interconnected quality control network, highlighting the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
193
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(204 citation statements)
references
References 158 publications
(167 reference statements)
3
193
0
Order By: Relevance
“…Mitochondrial i-AAA protease Yme1L locates at mitochondrial inner membrane and regulates quality control of mitochondrial proteins. [19][20][21][22] To clarify how Mic60/Mitofilin is degraded in mitochondria, we check the relationship between Yme1L and Mic60/Mitofilin. As WT Yme1L interacts and reacts with its substrates transiently, we mutated the glutamate residue of HEXXH motif, which is required for proteolysis in human Yme1L to glutamine (E600Q), and the mutant Yme1L-E600Q binds to its substrates stably.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial i-AAA protease Yme1L locates at mitochondrial inner membrane and regulates quality control of mitochondrial proteins. [19][20][21][22] To clarify how Mic60/Mitofilin is degraded in mitochondria, we check the relationship between Yme1L and Mic60/Mitofilin. As WT Yme1L interacts and reacts with its substrates transiently, we mutated the glutamate residue of HEXXH motif, which is required for proteolysis in human Yme1L to glutamine (E600Q), and the mutant Yme1L-E600Q binds to its substrates stably.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial inner membrane i-AAA protease Yme1L is a key regulator in the quality control of mitochondrial proteins. 19 Yme1L exerts ATPdependent proteolytic activity, resulting in either degradation or processing of its substrates such as optic atrophy 1 (OPA1) and some subunits of oxidative phosphorylation. [20][21][22] Mitochondria are dynamic organelles whose morphology are determined by continuous fusion and fission events.…”
mentioning
confidence: 99%
“…The lack of a strict sequence requirement, as revealed by the OOP structure, allows the cleavage of a wide range of substrates, constrained only by the peptide length. Within mitochondria and chloroplasts, a network of proteases (Lon, Deg, ClpP, and FtsH) is involved in the degradation of unfolded and damaged proteins, working as a quality control system (45). Proteases such as ClpP and Deg were shown to generate short peptide fragments up to 25 aa in length, with the majority being 5-12 and 9-20 aa, respectively (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our laboratory have shown that Surf1 −/− mice have reduced fat mass, improved insulin sensitivity, and enhanced memory, compared to wild‐type ( Surf1 +/+ ) mice (Deepa et al., 2013; Lin et al., 2013). In addition, tissues from Surf1 −/− mice show increased mitochondrial biogenesis and induction of the mitochondrial unfolded protein response (UPRmt), an evolutionarily conserved stress response pathway (Baker, Tatsuta & Langer, 2011). Fibroblasts from Surf1 −/− mice also show increased resistance to cellular stresses (Pharaoh et al, 2016; Pulliam et al., 2014) suggesting that reduced COX activity induces compensatory mitochondrial stress response pathways.…”
Section: Introductionmentioning
confidence: 99%